HUBUNGAN BEBAN KERJA FISIK, FREKUENSI OLAHRAGA, LAMA TIDUR, WAKTU ISTIRAHAT DAN WAKTU KERJA DENGAN KELELAHAN KERJA (Studi kasus pada pekerja Laundry Bagian Produksi Di CV.X Tembalang, Semarang) - Narpati, Jalu Risang; Ekawati, Ekawati; Wahyuni, Ida (Jurnal Kesehatan Masyarakat (Undip), 2019)
Fatigue is a feeling of fatigue that results in a decrease in mental and physical performance. The usual fatigue is a problem with lack, interest, and even decreased capacity. Fatigue in workers can reduce alertness and cause accidents. The current variable is working. While the independent variables are workload, exercise, sleep, rest time and work time. The purpose of this study is to Analyze Physical Work Relationships, Frequency of Sports, Sleep Length, Rest Time and Fatigue Working Time Working on Production Laundry Laundry Workers at CV. X Tembalang, Semarang. This type of research is a descriptive analytic study with a cross sectional study approach. This research instrument uses IFRC questionnaire. The sample in the study were 36 production workers with total sampling method. The prevalence measurement results were 80.6%. Based on the results of the Chi-Square statistical test, it shows that the independent variables are freely variable, namely between work with workload (p = 0,000), exercise frequency (p = 0,003), bedroom (p = 0,005), rest time (p = 0.005) and work time (p = 0.003). Suggestions for parties are as much as one minute for 1-2 minutes every 30 minutes of work and a minimum rest of 30 minutes after 4 hours of work to avoid tension and work that allows to optimize and ensure that the time needed to work can be reduced.